Field Phenotyping Strategies and Breeding for Adaptation of Rice to Drought† - Fukai, Shu; Fischer, Ken S. (Frontiers in Physiology, 2012)
This paper is a section of the book ‘Drought phenotyping in crops: from theory to practice (Monneveux Philippe and Ribaut Jean-Marcel eds, published by CGIAR Generation Challenge Programme. Texcoco, Mexico). The section describes recent experience in drought phenotyping in rice which is one of the most drought susceptible crops. The section contains genetic and genomic resources for drought adaptation and methods for selection of drought resistant varieties in rice. In appendix, there is experience from Thailand on integration of direct selection for grain yield and physiological traits to confer drought resistance.